O ódio nas redes sociais: uma investigação psicossocial à luz da teoria dos afetos de Espinosa - NASCIMENTO, Jasmine Marlena de Sousa (2023)
A few years ago, a series of authors noticed a growing exacerbation of hatred in digital social networks, manifested in subjects who incite speeches and practices of hatred towards the other. Based on Spinoza's theory of affections, we can conceive this hatred of the other practiced as the affect of sadness while we are aware of it, generated by a limited understanding, based only on the affections arising from signs or images that affect us, reducing our power to act and weakening our conatus. In view of this, we question: what elements cross the production of subjectivities driven by hate in digital social networks? In order to respond, the methodology used will be a bibliographical review of Espinosa's works, of his commentators, as well as psychosocial studies on social networks in contemporary times. The analysis of the subjectivities crossed by the affection of hate started from the social networks Facebook, Instagram, Twitter, YouTube and WhatsApp, where we found that this movement on the internet, of using social networks to propagate their hateful subjectivities, slips in the superficiality that these users are immersed in , the result of ignorance arising from the first kind of knowledge and its images and signs that are elements that falsify the imagination and that cross these subjectivities on these platforms, mainly from the elimination and removal of what diminishes their power to act and exist. Social networks give these users an illusory idea, which is nothing more than the algorithm that controls the information these people receive. This illusory idea results in these users the affect of joy, floating and provisional, as it is enough for another image that does not match their self-image to affect the bodies of these users again, for them to be taken over and dominated by the affect of sadness once again. The posts analyzed in this work reveal the cause of the sadness of users who made offensive comments, with the aim of inferiorizing and reducing the other. The hate speeches propagated by these users constitute their effort to persevere in their own being, carrying out the search movement to destroy the cause that saddens them, and precisely because of this, that hatred in Espinosa is useful in the connection with fear. , and because they are political and social affections, they end up contributing as a way of governing and manipulating people. And nothing is more facilitating and strategic than using social networks to enhance this movement, showing the desire to seek to offend and belittle others who are different in some way or who do not share the same thoughts and ideals. These subjectivities crossed by the affect of hate demonstrated in the posts analyzed in this work, are marked by the affects that derive from sadness and, therefore, constitute social and political affects that can be used for the control and modulation of contemporary societies.